The emissivity of the turbine engine powered by biofuel - Jacek Pielecha; Remigiusz Jasiński; Jarosław Markowski (Advances in Mechanical and Materials Engineering, 2017)
Air transport is the youngest and most dynamically developing branch of transport. Growth in demand for air transport, both passenger and freight, is caused by the competitiveness of this branch primarily in terms of time and transport safety. An increase in the volume of air traffic is associated with increased emissions, which is particularly important in the case of aircraft operations in the areas of airports. The main reason for the development of aircraft engines is the reduction of fuel consumption and exhaust emissions. Emission standards for aircraft engines certification marginally treat the issue of particulate matter emissions, which is associated with deterioration of visibility appearing as smog and contributes to lung and heart diseases. One of the solutions for limiting the negative impact of the aircraft on the environment is the use of alternative fuels. Production of biofuels in accordance with the principles of sustainable development, is an attractive alternative, especially because of the lack of space constraints of their production allows the geographical diversification of supply. The article presents the measurements results of jet engine GTM-120 exhaust emissions. The test engine was powered with Jet A-1 fuel with 50-percent addition of bioester. During the test concentration of carbon monoxide, hydrocarbons and particulate matter was measured. On the basis of the measurements, the effect of the use of biofuel on emissions was presented.